(untitled) (Educational Perspectives Magazine (REPED), 2023)
This article is the result of a final, though not conclusive, reflection of a research project “The Knowledge of the teacher: Analysis of the teacher training contents” (SOC 04/25-02) Research Department, Vice-chancellor’s office of Research and Development, Universidad de Chile. The paper is an analysis of contemporary teaching reflections, the plausible scientific character of pedagogy and its consequences for professional teaching and training. On the basis of an updated bibliographical account, the contributions of eight consulted Chilean experts support this analysis. Their vast experience in the field of the history and development of the teaching profession is brought together, as well as their thoughts in relation to the challenges facing teacher training transformation in today’s complex society. Towards the end of the article, both conceptual and methodological difficulties are anticipated to be solved regarding the construction of teachers’ knowledge and the Identification of their professional competencies.